3x 5 2x 2 x 3
![3x 5 2x 2 x 3](https://media.cheggcdn.com/media/a98/a986495c-7c50-4bce-aa84-69a5748f095e/phpTUUZbq.png)
- 3x 2 2x 5 )= 2 x 3 )- 8
- 3x 5 2 2x 1 )+( x 3
- 3x 1 2 2x 5 3 x 3 6
- 3x 2 2x 5 )( 3x 2 x 2
- 5 2 x )= 3 2x 7 3x
- 3x 4 2 2x 1 5 8 x 3
- F x )= 5 2x 2 3x 4 2x x 3
- 3x 2 x 2 )= 22 3 2x 5
- 2x 1 3 5 3x 2 x 7 4
- 3x 1 )( 2x 5 )=( 3x 1 )( x 2
- 3x 5 )( 2x 1 )=( 6x 2 )( x 3
- 2x 3 4 3x 5 2 x 3 4
- 3x 2 2x 5 )= 2 x 3 )- 8 solution
- 3x 2 2x 5 )= 2 x 3 )- 8 answer
- 3x x 5 )- 2x 6 2 x 3